Una mirada a la productividad laboral para las pymes de confecciones (2015)
The interest for the productivity, and specifically by labor productivity has increased, the motivation lies in finding the most influential aspects to improve organizational productivity. The aim is to highlight the need for a model to increase labor productivity in SMEs in the clothing industry. This paper is looking for relevant information to construct that model; it will build to the context of the metropolitan area of Bucaramanga, Santander. The research raises labor productivity from the approaches of the economy, administration and engineering. This productivity is vital for organizations; even more for SMEs has given their need for orientation and its impact on income and the employment at the national level. Throughout the history of Bucaramanga the clothing industry has been regarded as strategic, for this reason is relevant manage their labor productivity to impact local development. This paper highlights the main aspects to consider for the future construction of the model mentioned.